Personalized medicine, public health and patient-centred aspects in the prevention of stroke in intracerebral haemorrhage survivors with atrial fibrillation (PRESTIGE-AF) project - Harvey, Kirsten; Korompoki, Eleni; Harvey, Emily R.; Fießler, Cornelia; Malzahn, Uwe; Hügen, Klemens; Ullmann, Sabine; Schuhmann, Carolin; Todd, Gabriele Putz; Montaner, Joan; Penalba, Anna; Guaman-Pilco, Daisy; et al. (Thrombosis and haemostasis, 2025)
Thieme E-Books & E-Journals